GARP for Kids: On the Development of Rational Choice Behavior - Harbaugh, William T; Krause, Kate; Berry, Timothy R (American Economic Review, 2001)
GARP for Kids: On the Development of Rational Choice Behavior by William T. Harbaugh, Kate Krause and Timothy R. Berry. Published in volume 91, issue 5, pages 1539-1545 of American Economic Review, December 2001